In Situ Transfection by Controlled Release of Lipoplexes Using Acoustic Droplet Vaporization. Issue 14 (18th May 2016) - Juliar, Benjamin A.; Bromley, Melissa M.; Moncion, Alexander; Jones, Denise C.; O'Neill, Eric G.; Wilson, Christopher G.; Franceschi, Renny T.; Fabiilli, Mario L.
Abstract : Localized delivery of nucleic acids to target sites (e.g., diseased tissue) is critical for safe and efficacious gene therapy. An ultrasound‐based technique termed acoustic droplet vaporization (ADV) has been used to spatiotemporally control the release of therapeutic small molecules and proteins contained within sonosensitive emulsions. Here, ADV is used to control the release of lipoplex—containing plasmid DNA encoding an enhanced green fluorescent protein reporter—from a sonosensitive emulsion. Focused ultrasound (3.5 MHz, mechanical index (MI) ≥ 1.5) generates robust release of fluorescein (i.e., surrogate payload) and lipoplex from the emulsion. In situ release of the lipoplex from the emulsion using ADV (MI = 1.5, 30 cycles) yields a 55% release efficiency, resulting in 43% transfection efficiency and 95% viability with C3H/10T1/2 cells. Without exposure to ultrasound, the release and transfection efficiencies are 5% and 7%, respectively, with 99% viability. Lipoplex released by ADV retains its bioactivity while the ADV process does not yield any measureable sonoporative enhancement of transfection. Co‐encapsulation of Ficoll PM 400 within the lipoplex‐loaded emulsion, and its subsequent release using ADV, yield higher transfection efficiency than the lipoplex alone. The results demonstrate that ADV can have utility in the spatiotemporal control of gene delivery. Abstract : An ultrasound‐based technique called acoustic droplet vaporization (ADV) is used to control the release of a lipoplex—containing plasmid DNA— from a sonosensitive double emulsion. The lipoplex is encapsulated into the emulsion and released by ADV without affecting its bioactivity. Significantly greater transfection is observed following ADV, which demonstrates that ADV could have utility in spatiotemporal control of gene delivery.